Permanences of fleeting Venice: three acts and an epilogue in the urban scenography of San Marco. - García Pérez, Francisco Antonio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
It is tackled the study of three ephemeral events that took place in the most theatrical urban space of the city of Venice: the short life of a fountain built on Piazza di San Marco in 1884, the unexpected fall of the Campanile in 1902 and the multitudinous concert that Pink Floyd gave on a floating stage in 1989. It is argued that each of these three events uncovered a series of issues relating to the treatment of architectural and urban heritage that will mark the future of the image of The City of Canals.
Keywords: Ephemeral Architecture; Campanile; Commemorative Fountain; Pink Floyd; San Marco; Venice